Prevalence of atherosclerosis risk factors in Egyptian patients with acute coronary syndrome: final data of the nationwide cross-sectional 'CardioRisk' project - Ashraf Reda; Ahmed Bendary; Atef Elbahry; Elsayed Farag; Tamer Mostafa; Hazem Khamis; Moheb Wadie; Mohamed Bendary; Basant A. Azeem; Rehab Salah (AOSIS, 2020)
Background: Little are known about the prevalence of atherosclerosis risk factors in Egyptian patients with acute coronary syndromes (ACS). Objective: Describe the prevalence of these risk factors with focus on gender-specific data and patients with premature presentation. Methods: From November 2015 to August 2018, data were collected from 3224 patients with ACS in 30 coronary care centers covering 11 governorates across Egypt, with focus premature ACS. Results: The vast majority were males (74%) and the most prevalent age group was (56-65 years) representing 37% of whole study population. Among female patients, 92% were post-menopausal. The prevalence of premature ACS was 51%. Forty five percent of total males and 69.6% of total females with ACS had premature presentation (P0.001). Abdominal obesity was the most prevalent risk factor (66%). Nearly half of the entire study patients were current smokers (48%). We showed a high prevalence of documented dyslipidemia (48%) as well. Early invasive management strategy was employed in 65% of patients with no significant gender disparity noticed. Vascular access for coronary angiography was most commonly femoral (80% of time). Emergent percutaneous coronary intervention (PCI) was attempted in 53% of patients. Thrombolytic therapy (using Streptokinase) was used in 24% of included participants. Conclusion: Among Egyptian patients with ACS, premature presentation is common with greater male preponderance. Abdominal obesity is the most prevalent risk factor followed by hypertension. Most traditional risk factors (apart from smoking) were more prevalent in women than men.